Noun phrase complexity in Ghanaian English. Issue 3 (3rd April 2020) - Brato, Thorsten
Abstract: This study compares the complexity of the noun phrase (NP) in Ghanaian English in a real‐time perspective. Based on the Historical Corpus English in Ghana (1966–1975) and the Ghanaian component of the International Corpus of English (mainly 2000s), representing the early and late stages of structural nativisation in the dynamic model, NP complexity is measured using five criteria (NP pattern, complexity of the premodifier, length of the pre‐ and postmodifier and complexity of the postmodifier). The study uses conditional inference trees, taking into account three potential factors: corpus, text type and syntactic function. The results show that over time the complexity of the NP in Ghanaian English has increased, which is interpreted as Ghanaians becoming more proficient and therefore employing more sophisticated structures. Text type is an important predictor; syntactic function plays only a minor role. By adding a diachronic perspective, the study contributes to current models of the evolution of world Englishes.